Differential roles of NADPH oxidases in vascular physiology and pathophysiology - Amanso, Angelica M. (2012)
Reactive oxygen species (ROS) are produced by all vascular cells and regulate the major physiological functions of the vasculature. Production and removal of ROS are tightly controlled and occur in discrete subcellular locations, allowing for specific, compartmentalized signaling. Among the many sources of ROS in the vessel wall, NADPH oxidases are implicated in physiological functions such as control of vasomotor tone, regulation of extracellular matrix and phenotypic modulation of vascular smooth muscle cells. They are involved in the response to injury, whether as an oxygen sensor during hypoxia, as a regulator of protein processing, as an angiogenic stimulus, or as a mechanism of wound healing. These enzymes have also been linked to processes leading to disease development, including migration, proliferation, hypertrophy, apoptosis and autophagy. As a result, NADPH oxidases participate in atherogenesis, systemic and pulmonary hypertension and diabetic vascular disease. The role of ROS in each of these processes and diseases is complex, and a more full understanding of the sources, targets, cell-specific responses and counterbalancing mechanisms is critical for the rational development of future therapeutics.